Regional lymph node sampling in hepatoma resection: insight into prognosis. Issue 9 (September 2021) - Bergquist, John R.; Li, Amy Y.; Javadi, Christopher S.; Lee, Byrne; Norton, Jeffrey A.; Poultsides, George A.; Dua, Monica M.; Visser, Brendan C.
Abstract: Background: The importance of regional lymph node sampling (LNS) during resection of hepatocellular carcinoma (HCC) is poorly understood. This study sought to ameliorate this knowledge gap through a nationwide population-based analysis. Methods: Patients who underwent liver resection (LR) for HCC were identified from Surveillance, Epidemiology and End Results (SEER-18) database (2003–2015). Cohort-based clinicopathologic comparisons were made based on completion of regional LNS. Propensity-score matching reduced bias. Overall and disease-specific survival (OS/DSS) were analyzed. Results: Among 5395 patients, 835 (15.4%) underwent regional LNS. Patients undergoing LNS had larger tumors (7.0vs4.8 cm) and higher T-stage (30.9 vs. 17.6% T3+, both p < 0.001). Node-positive rate was 12.0%. Median OS (50 months for both) and DSS (28 vs. 29 months) were similar between cohorts, but node-positive patients had decreased OS/DSS (20/16 months, p < 0.01). Matched patients undergoing LNS had equivalent OS (46 vs. 43 months, p = 0.869) and DSS (27 vs. 29 months, p = 0.306) to non-LNS patients. The prognostic impact of node positivity persisted after matching (OS/DSS 24/19 months, p < 0.01). Overall disease-specific mortality were both independently elevated (overall HR 1.71-unmatched, 1.56-matched, p < 0.01; disease-specific HR 1.40-unmatched, p < 0.01, 1.25-matched, p = 0.09). Conclusion: Regional LNS is seldom performed during resection for HCC, but it provides useful prognostic information. As the era of adjuvant therapy for HCC begins, surgeons should increasingly consider performing regional LNS to facilitate optimal multidisciplinary management. Graphical abstract: Image 1